Microencapsulated Chitosan-Based Nanocapsules: A New Platform for Pulmonary Gene Delivery - Estefanía Fernández-Paz; Lucía Feijoo-Siota; Maria Manuela Gaspar; Noemi Csaba; Carmen Remuñán-López (MDPI AG, 2021)
In this work, we propose chitosan (CS)-based nanocapsules (NCs) for pulmonary gene delivery. Hyaluronic acid (HA) was incorporated in the NCs composition (HA/CS NCs) aiming to promote gene transfection in the lung epithelium. NCs were loaded with a model plasmid (pCMV-βGal) to easily evaluate their transfection capacity. The plasmid encapsulation efficiencies were of approx. 90%. To facilitate their administration to the lungs, the plasmid-loaded NCs were microencapsulated in mannitol (Ma) microspheres (MS) using a simple spray-drying technique, obtaining dry powders of adequate properties. In vivo, the MS reached the deep lung, where the plasmid-loaded CS-based NCs were released and transfected the alveolar cells more homogeneously than the control formulation of plasmid directly microencapsulated in Ma MS. The HA-containing formulation achieved the highest transfection efficiency, in a more extended area and more homogeneously distributed than the rest of tested formulations. The new micro-nanostructured platform proposed in this work represents an efficient strategy for the delivery of genetic material to the lung, with great potential for the treatment of genetic lung diseases.